1997
DOI: 10.1111/j.1365-2249.1997.258-ce1131.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of Epstein–Barr virus (EBV) lymphoblastoid cell line-reactive lymphocytes in cord blood: evaluation of cytolytic activity and IL-2 production

Abstract: SUMMARYWe investigated natural immunity towards autologous EBV lymphoblastoid cell lines (EBV-LCL) in the cord blood. Cord blood lymphocytes (CBL) from 20 healthy neonates were examined together with three EBV and one EBV ÿ adult donors. We found that high frequencies of EBV-LCL-reactive cytotoxic lymphocytes, ranging from 1/190 to 1/12 205 were detectable in EBV donor. These data demonstrate that CBL are able to develop a strong innate immunity, directed against autologous EBV-infected cells, mediated by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
3
24
1
Order By: Relevance
“…Moreover, a persistence of this unique pattern of cord blood cytolytic response towards NIMA after the perinatal period could possibly explain why recipients of renal transplants from a HLA-haploidentical NIMA-disparate sibling enjoy a longer graft survival than patients given the kidney from a donor diverse for NIPA. 29 In keeping with previously published data demonstrating that autologous EBV-LCL are able to elicit in CBMC a strong innate immunological response mediated by both NK cells and CD4 + T lymphocytes, 43 our present data demonstrate that a similar preferential expansion of NK subsets can also be observed after activation with allogeneic EBV-LCL, and confirm evidence on the strong functional capacity of cord blood NK cells, when activated by some viral stimuli. 43 It has been reported that in humans EBV-specific immune responses may generate a CTL-mediated crossreaction with alloantigens, 44 this explains the clinical association between herpesvirus infections and GVHD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, a persistence of this unique pattern of cord blood cytolytic response towards NIMA after the perinatal period could possibly explain why recipients of renal transplants from a HLA-haploidentical NIMA-disparate sibling enjoy a longer graft survival than patients given the kidney from a donor diverse for NIPA. 29 In keeping with previously published data demonstrating that autologous EBV-LCL are able to elicit in CBMC a strong innate immunological response mediated by both NK cells and CD4 + T lymphocytes, 43 our present data demonstrate that a similar preferential expansion of NK subsets can also be observed after activation with allogeneic EBV-LCL, and confirm evidence on the strong functional capacity of cord blood NK cells, when activated by some viral stimuli. 43 It has been reported that in humans EBV-specific immune responses may generate a CTL-mediated crossreaction with alloantigens, 44 this explains the clinical association between herpesvirus infections and GVHD.…”
Section: Discussionsupporting
confidence: 92%
“…29 In keeping with previously published data demonstrating that autologous EBV-LCL are able to elicit in CBMC a strong innate immunological response mediated by both NK cells and CD4 + T lymphocytes, 43 our present data demonstrate that a similar preferential expansion of NK subsets can also be observed after activation with allogeneic EBV-LCL, and confirm evidence on the strong functional capacity of cord blood NK cells, when activated by some viral stimuli. 43 It has been reported that in humans EBV-specific immune responses may generate a CTL-mediated crossreaction with alloantigens, 44 this explains the clinical association between herpesvirus infections and GVHD. The preferential early activation of NK cord blood cells, instead of CTL, in response to some viral infections, similar to that observed after NIMA challenge, may also contribute to the low incidence and severity of GVHD in CBT recipients.…”
Section: Discussionsupporting
confidence: 92%
“…The effector cells from the seronegative adults are true CTL, showing clear evidence of MHC restriction and target cell specificity. Several investigators have previously reported that LCL can enhance NK or LAK activity in EBV-seronegative donors, and apparent EBVspecific cytotoxic activity obtained from seronegative donors has often not been clearly differentiated from NK-or LAK-mediated activity (17,33,35). We observed a similar phenomenon in three of our seronegative children from whom cytolytic T cell lines were elicited using the standard protocol.…”
Section: Discussionsupporting
confidence: 75%
“…EBV-specific CTL can be reactivated from EBV-seropositive individuals by stimulation of peripheral blood T cells with autologous irradiated EBV-transformed lymphoblastoid B cell lines (LCL) (11,16). Although LCL are potent APCs, they seem incapable of inducing a primary immune response to EBV in vitro (11)(12)(13)(14)(15)(16)(17). This has been a major problem for the high-risk seronegative recipients of EBV-seropositive organ grafts, who are the individuals most at risk (8).…”
mentioning
confidence: 99%
“…35 Briefly, fresh PBMC or cells recovered from primary MLC were seeded in a final volume of 200 l in 96-well round-bottom microplates. Decreasing numbers of responder cells (10 4 , 5 ϫ 10 3 , 2.5 ϫ 10 3 , 1.25 ϫ 10 3 , 0.6 ϫ 10 3 ) were stimulated with 10 4 autologous irradiated (7000 rads) B-LCL.…”
Section: Limiting Dilution Assay For Evaluation Of Cmv-and Ebvspecifimentioning
confidence: 99%